The future research methods in sociological field Systematic study - Diaby, Hanan (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The study aimed to determine the forward-looking scientific methods through systematic methods, methods and tools used in the outlook studies employing the sociological field study, and conduct a systematic approach and study of the tools and techniques for studies forward-looking, in order to develop methods of social research for the study of the social phenomenon is forward-looking, through the study and analysis of the past and understand the present to influence the future, since the future is the time that we can control him If we had scientific knowledge and if we want to influence him through scenarios and alternatives help to cope with unforeseen circumstances and avert a crisis mode, so the study provided a systematic model for social studies forward-looking, the importance of the outlook studies in time current and especially after the information technology and communications revolution, the current world is the world of the future and if we want to influence where we study the present in accordance with the forward-looking data (to draw our future as we want), and this can only be achieved through scientific study in accordance with the methodology steps.